(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Social entrepreneurship is a promising approach to addressing social and environmental challenges. Family-owned ventures have emerged as one of the most important forms of entrepreneurship in the last few decades. In the framework of family-owned businesses, this paper examines the significance of social impact strategies and how they contribute to the development of sustainable entrepreneurship. The study collects data through in-depth interviews using a qualitative research methodology. The goal of the study is to close some of the gaps in the literature that it focuses on. An overview of the body of literature is provided at the end of the article, which can be used as a starting point for comprehending the concepts and theoretical underpinnings of social ventures.